2020
DOI: 10.1089/ham.2019.0111
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Mild Cognitive Impairment with Ascending Altitude

Abstract: Background: This study aimed to longitudinally quantify the prevalence of mild cognitive impairment (MCI) in individual trekkers at three different ascending altitudes (Site 1: *3500 m, Site 2: *4400 m, and Site 3: *5100 m). We correlated these findings with the presence of acute mountain sickness (AMS). Materials and Methods: We performed serial assays using the environmental quick mild cognitive impairment (eQMCI) score on 103 English-speaking 18-to 65-year-old volunteers trekking to Everest Base Camp in Nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…At present, numerous treatment methods such as drug treatment, psychotherapy, and surgery are utilized to treat the patients with MCI, and these treatment methods have certain protective effect in preventing or slowing the development progress of MCI. However, the study by Overton M reports that nearly 30% of patients with MCI will develop to Alzheimer's disease, and Alzheimer's disease will cause greater damage to health, cognitive function, memory function, and lives in patients (Algaze et al, 2020; Overton et al, 2019). How to choose an appropriate method to prevent MCI development is an urgent problem to solve.…”
Section: Discussionmentioning
confidence: 99%
“…At present, numerous treatment methods such as drug treatment, psychotherapy, and surgery are utilized to treat the patients with MCI, and these treatment methods have certain protective effect in preventing or slowing the development progress of MCI. However, the study by Overton M reports that nearly 30% of patients with MCI will develop to Alzheimer's disease, and Alzheimer's disease will cause greater damage to health, cognitive function, memory function, and lives in patients (Algaze et al, 2020; Overton et al, 2019). How to choose an appropriate method to prevent MCI development is an urgent problem to solve.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it was reported that high altitude could induce irreversible/reversible damage to high oxygen and energy demanding tissues, such as the brain, heart, liver, gastrointestinal tract, and ocular tissue, over a certain period of time (15)(16)(17)(18)(19)(20). The clinical characteristics commonly include blood pressure fluctuation, loss of memory function (declined cognitive function), absence of equilibrium function, headache, indigestion, decreased appetite, and so on (21)(22)(23)(24).…”
Section: High-altitude Heart Diseasesmentioning
confidence: 99%
“…Deyar reported that Air Force crew members exposed to a simulated HA of 20000 feet (equivalent to 6096 meters) for 15 minutes suffered from rapid learning and memory de cits, although visual and auditory memory were basically preserved with little change (Deyar et al, 2013). Short-term memory decreased following exposure to chronic hypoxia at 4400 m, and this effects was exacerbated as the altitude increased (Algaze et al, 2020). Therefore, the adverse effects of acute hypoxia exposure require e cient interventions to protect human cognitive functions.…”
Section: Introductionmentioning
confidence: 99%